Characterization of ML-005, a Novel Metaproteomics-Derived Esterase - Sukul, Premankur; Lupilov, Natalie; Leichert, Lars I. (Frontiers in Microbiology, 2018)
A novel gene encoding for a lipolytic enzyme, designated ML-005, was recently identified using a functional metaproteomics approach. We heterologously expressed this protein in E. coli and biochemically characterized it. ML-005 exhibited lipolytic activity towards short chained substrates with the prefered substrate being p-nitrophenyl-butyrate, suggesting that ML-005 is an esterase. According to homology analysis and site-directed mutagenesis, the catalytic triad of the enzyme was identified as Ser-99, Asp-164, and His-191. Its optimal pH was determined to be at pH 8. Optimal activity was observed at 45°C. It also exhibited temperature, pH and salt tolerance. Residual relative activity after incubating at 50-60°C for 360 minutes was above 80% of its initial activity. It showed tolerance over a broad range of pH (5-12) and retained most of its initial activity. Furthermore, incubating ML-005 in 1M - 5M NaCl solution had negligible effect to its activity. DTT, EDTA and ß-mercaptoethanol had no significant effect on ML-005’s activity. However, addition of PMSF led to almost complete inactivation consistent with ML-005 being a serine hydrolase. ML-005 remains stable in the presence of a range of metal ions, however, addition of Cu2+ reduces its relative activity by up to 50%. Organic solvents have an inhibitory effect on ML-005 but it retained 21% of activity in 10% methanol. SDS had the most pronounced inhibitory effect on ML-005 among all detergents and completely inactivated it. Furthermore, the Vmax of ML-005 was determined to be 59.8 µM/min along with a Km of 137.9 µM. The Kcat of ML-005 is 26 s^-1 and kcat/km is 1.88 * 10^5 M^-1 s^-1.